Reduced fertigation input sustains yield and physiological performance for improved economic returns and cleaner production of greenhouse eggplant - Md Mazadul, Islam (2024)
Greenhouse horticulture, a sustainable alternative to conventional horticulture, maximises resource use and return for vegetable production. This study evaluated the impact of varying nutrient solution electrical conductivity (EC) levels (EC 1.8, 2.8, and 3.8) on eggplant cultivars (Solanum melongena L. cv. Lydia, and Tracey) performance and economic viability in high-tech glasshouses. We found that morphological traits such as plant height and leaf number were consistent across EC levels, while fruit weight, length, and width are significantly higher at the lowest EC (1.8). Photosynthetic rates increased significantly with rising EC levels, while other gas exchange parameters such as stomatal conductance, intrinsic water use efficiency, and vapour pressure deficit were similar for all EC levels tested. Yield analysis revealed a negative correlation between eggplant yield and increasing EC levels, with optimal yields in both eggplant varieties (0.81 and 1.14 kg m−2 week−1 in Lydia and Tracey, respectively) achieved at the lowest EC. Economic analysis highlighted that lower EC levels lead to lower operational costs and higher net profit values (NPV). Sensitivity analysis underscored the importance of wholesale price and crop yield in determining NPV, with lower EC levels offering a shorter payback period of approximately 6 years in Australia and China and higher economic returns. The study highlights the significance of optimizing EC levels for achieving more resource-sustainable and profitable eggplant production in greenhouses.